PERENCANAAN DAN EVALUASI PROGRAM TRAINING - Mohamad Soedarman (Akutansi Bisnis & Manajemen ( ABM ), 2001)
When Should you evaluate training? The most people would respond by saying? at the end of the training of course!?. If that?s what you thought than, you may need to think again. Evaluation should be the first step, rather than the last. There are a simple model of training, generally referred to as the ?Training cycle?, and only then as a means of introducing a few ideas about measuring the success of a training event . In an attempt to overcome the problem of difficulty in identifying the results of management training, Warr, Bird and Rackham proposed what was than seen as a radical approach. Fundamentally, the nation was that ech stage of the training Cycle should be evaluated before moving on to a subsequent stage. Surveys of training program evaluation methods used by American businesses generally show, however, that most companies measure the impact of training by considering workers? reactions to the training, workers? learning from the training, or the impact of training on workers? behavior. Several of the companies convert the results from training into monetary terms in order to calculate an ROI on the training investment. The failure of most firms to calculate the ROI on their training investments appears to be due to the perceived difficulties in quantifyng training benefits, separating the influence of training on performance improvement from other factors, and gathering the data that are necessary for an ROI calculation. Table III and IV provides a summary of the cases for which the ROI in training at American businesses was calculated. For each company, the performance measure, and the estimated ROI s are shown. The main result that stand out from the tables are that the estimated ROIs are extremely high, ranging from 100 to 5900 percent.